PELATIHAN DAN MOTIVASI KERJA SEBAGAI DETERMINAN KINERJA KARYAWAN PT PITJARUS TEKNOLOGI DI BEKASI - Mohammad Alvin Mustofa (LPPM Sekolah Tinggi Ilmu Ekonomi Ganesha, 2023)
PT Pitjarus Teknologi is a company engaged in information technology and provides software services to its clients. The purpose of this research is to determine the influence of training and work motivation on employee performance at PT Pitjarus Teknologi located in Bekasi. The research method used is descriptive quantitative, utilizing questionnaires as the data collection method with 100 respondents from the employees of PT Pitjarus Teknologi. The data analysis used is statistical analysis using SPSS (Statistical Package for the Social Sciences) v26. The results of the research show that (1) there is a positive and significant influence of the training variable on employee performance at PT Pitjarus Teknologi, (2) there is a positive and significant influence of the work motivation variable on employee performance at PT Pitjarus Teknologi, and (3) there is a positive and significant influence of the environment and motivation variables on employee performance at PT Pitjarus Teknologi. The expectation from the implementation of this research is that PT Pitjarus Teknologi can improve employee performance by paying attention to the factors of enhancing training and work motivation. The originality/value of this research can be beneficial for employees in their efforts to improve their performance to be better.